2021
DOI: 10.21608/adjalexu.2020.33084.1082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immediate Implant Placement With a Modified Socket Shield Technique Using Xenogenic Bone Graft (A Randomized Controlled Clinical Trial)

Abstract: BACKGROUND: Modified Socket shield technique, is an approach used to help maintain buccal bone level after implant insertion. However, the significance of bone grafting of the gap between the labial shield and the implant, in improving bone regeneration and prevention of the soft tissue ingrowth, has been described. AIM OF THE STUDY: Evaluation of clinical and radiographic outcomes of using xenogenic bone graft on outcome of immediate dental implant placement using the modified socket shield technique. MATERIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…This means that fixing the mandibular fractures with reconstruction bone plate and filling the bone defect with the xeno-Hydroxyapetite bone graft is better as an increase in opacity indicated an increase in bone formation in the defect area (13) . This could be attributed to the fact that HA as a natural structure has low immunogenicity with low inflammatory response and good integration of HA (14) . In addition, it was reported that HA significantly prevents loss of bone after extraction in animal and human trials (15).…”
Section: Discussionmentioning
confidence: 99%
“…This means that fixing the mandibular fractures with reconstruction bone plate and filling the bone defect with the xeno-Hydroxyapetite bone graft is better as an increase in opacity indicated an increase in bone formation in the defect area (13) . This could be attributed to the fact that HA as a natural structure has low immunogenicity with low inflammatory response and good integration of HA (14) . In addition, it was reported that HA significantly prevents loss of bone after extraction in animal and human trials (15).…”
Section: Discussionmentioning
confidence: 99%